1996
DOI: 10.1016/0014-5793(96)00816-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the substrate specificity of MAPKAP kinase‐2 and MAPKAP kinase‐3 and their activation by cytokines and cellular stress

Abstract: MAPKAP kinase-2 and MAPKAP kinase-3 were both activated in response to cellular stress, interleukin-1 and tumour necrosis factor in KB and HeLa cells, and with identical kinetics. Activation of MAPKAP kinase-3, like MAPKAP kinase-2, was prevented by SB 203580, a specific inhibitor of SAPK-2, the upstream activator of MAPKAP kinase-2. MAPKAP kinase-3 and MAPKAP kinase-2 pbospborylated peptide substrates with similar kinetic constants and phospborylated the same serine residues in HSP27 at the same relative rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 134 publications
(125 citation statements)
references
References 22 publications
2
122
0
1
Order By: Relevance
“…The MAPKAP kinases MK2 and MK3 are highly similar in structure and function and, so far, no differences in their activation by p38 MAPK and their substrate specificity have been described [Clifton et al, 1996;Gaestel, 2006;Ronkina et al, 2007]. For MK2, a role in cell migration has been demonstrated which depends on its catalytic activity and on the integrity of its N-terminal proline-rich region [Kotlyarov et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MAPKAP kinases MK2 and MK3 are highly similar in structure and function and, so far, no differences in their activation by p38 MAPK and their substrate specificity have been described [Clifton et al, 1996;Gaestel, 2006;Ronkina et al, 2007]. For MK2, a role in cell migration has been demonstrated which depends on its catalytic activity and on the integrity of its N-terminal proline-rich region [Kotlyarov et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been demonstrated that this proline-rich motif of MK2 is essential for trans-well migration of smooth muscle cells and fibroblast in a Boyden chamber experiment [Kotlyarov et al, 2002]. MK2 and MK3 are indistinguishable in regard to p38-dependent regulation and activation as well as substrate specificity [Clifton et al, 1996]. Both, MK2 and MK3, can rescue p38 level, Hsp25-phosphorylation, cytokine mRNA-stability, and CXCL1 production in MK2-deficient mouse embryonic fibroblasts [Ronkina et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Epidermal growth factor (EGF) was purchased from Boehringer Mannheim and the monoclonal anti-H-Ras antibody (Y13 259) from Oncogene Science Products. The antibodies against c-Raf ( Alessi et al, 1995b), MAPKAP kinase-2 (Clifton et al, 1996), MAP kinase kinase-1 (MKK1) and MAPK2 (also called ERK2) were raised in sheep at the Scottish Antibody Production Unit (Carluke, Lanarkshire, UK). The anti-MKK1 antibodies were raised against the peptide PKKKPTPIQLNPAPDG correspond-ing to residues 2 ± 17 and the anti-MAPK2 antibodies against the C-terminal peptide ± EETARFQPGYRS.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoprecipitation of protein kinases c-Raf was immunoprecipitated from 400 mg cell lysate protein, MKK1 from 100 mg of cell lysate and MAPK2 and MAPKAP kinase-2 from 50 mg cell lysate protein using 5 ml of protein GSepharose conjugated to 4 mg of the appropriate antibody (Alessi et al, 1995b;Clifton et al, 1996).…”
Section: Cell Culture and Stimulationmentioning
confidence: 99%
See 1 more Smart Citation